Answer:
1. 60 2. 200
Step-by-step explanation:
600÷10= 60
2000÷10=200
Answer:
60 and 200
Step-by-step explanation:
When divideing by 10 you can cancel the zeros from both the numertor and denominator
Solve x2+6x=7 by completing the square.Which is the solution set of the equation?
Answer:
x = - 7, x = 1
Step-by-step explanation:
Given
x² + 6x = 7
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(3)x + 9 = 7 + 9
(x + 3)² = 16 ( take the square root of both sides )
x + 3 = ± [tex]\sqrt{16}[/tex] = ± 4 ( subtract 3 from both sides )
x = - 3 ± 4
x = - 3 - 4 = - 7
x = - 3 + 4 = 1
Solution set = { - 7, 1 }
I hate simplifying Radicals. Square root 180 divided by 6.
Answer:
2.2360679775 or 2.24
Step-by-step explanation:
Because the square root of 180 is 13.416407865 and when you divide that by 6 you will get 2.2360679775 or 2.24
What is 1/2+3/8+3/2 equal with commutative property
Answer:
[tex]\frac{19}{8}[/tex]
Step-by-step explanation:
As per definition of commutative property, the final output of addition remains same regardless to what order the number are added in i.e.
[tex]a + b + c = b + c + a = c + a + b[/tex]
∴[tex]\frac{1}{2} + \frac{3}{8} + \frac{3}{2} = \frac{4 + 3 + 12}{8} = \frac{19}{8}[/tex]
Solve
6(x-2)-4x=8+2x-20
What is the equation of a line that contains the point (4, 0) and is parallel to x + y = 2?
Answer:
x + y = 4 or y = -x + 4
Step-by-step explanation:
0 = -1[4] + b
4 = b
y = -x + 4
If you want it in Standard Form:
y = -x + 4
+x +x
_________
x + y = 4 >> Line in Standard Form
* Since the rate of change [slope] is -1 and that parallel lines have SIMILAR SLOPES, -1 remains the same.
I am joyous to assist you anytime.
How many 4 1/2 meters of ribbon are there in a 140 meter spool?
Answer:
in a 140 meter spool there are 31 1/9 times 4 1/2 meters of ribbon
Step-by-step explanation:
To find out how many 4 1/2 meters of ribbon are there in a 140 meter spool, divide 140 meter by 4 1/2 meter, but first convert mixed number to an improper fraction
[tex]4\frac{1}{2}=\frac{4*2+1}{2}=\frac{9}{2}[/tex]
[tex]\frac{140}{(9/2)}=\frac{280}{9}[/tex]
Convert to mixed number
[tex]\frac{280}{9}=\frac{279}{9}+\frac{1}{9}=31\frac{1}{9}\ times[/tex]
therefore
in a 140 meter spool there are 31 1/9 times 4 1/2 meters of ribbon
The equation d=m/v can be used to calculate the density
Solve w=x+y/z for y AND z
y/z is a fraction NOT dividing
w= x + y/z
w-x = y/z
z= y/(w-x)
y = (w-x)z
Fractions are division problems, ex 1/2 is the same as one divided by 2, so if you multiply the denominator you solve for the numerator, and to solve for the denominator just substitute what's on the other side
7. Change the fraction 13/20 to a decimal.
Answer:
divide it using a calculator
Answer:
Step-by-step explanation:
0.65 is your answer
Triangle E F G is shown. Which statements regarding Triangle E F G are true? Select three options. E F + F G greater-than E G E G + F G greater-than E F E G minus F G less-than E F E F minus F G greater-than E G E G + E F less-than F G
The properties of triangle side lengths follow the Triangle Inequality Theorem, which states that the sum of any two sides of a triangle must be greater than the third side, leading to three correct inequalities for Triangle EFG.
Explanation:The question presented is related to the properties of triangle sides, specifically in relation to the inequality theorems that apply to triangles.
By understanding these properties, we can determine which statements about the lengths of the sides in triangle EFG are true.
The Triangle Inequality Theorem states that the sum of the lengths of any two sides of a triangle must be greater than the length of the third side.
This theorem gives rise to three inequalities that must hold true for any triangle:
EF + FG > EGEG + FG > EFEG + EF > FGTo assess which statements about Triangle EFG are true, we can compare them against the principles derived from the Triangle Inequality Theorem.
The following are the correct statements based on this theorem:
EF + FG > EGEG + FG > EFEG - FG < EFAny statement that contradicts these principles is false.
Therefore, the three true statements regarding Triangle EFG are that EF + FG is greater than EG, EG + FG is greater than EF, and EG - FG is less than EF.
The three true statements regarding Triangle EFG are:
- EF + FG > EG
- EG + FG > EF
- EG + EF < FG
Let's go through each option one by one:
1. E F + F G greater-than E G: To determine if this statement is true, we need to compare the lengths of EF and EG combined with FG. Let's say EF is 5 units long, FG is 3 units long, and EG is 7 units long. In this case, 5 + 3 is equal to 8, which is greater than 7. Therefore, this statement is true.
2. E G + F G greater-than E F: Similarly, to determine if this statement is true, we need to compare the lengths of EG and FG combined with EF. Using the same lengths as before, 7 + 3 is equal to 10, which is greater than 5. Therefore, this statement is true as well.
3. E G minus F G less-than E F: For this statement, we need to subtract the length of FG from EG and compare it to EF. Using the same lengths as before, 7 - 3 is equal to 4, which is less than 5. Therefore, this statement is false.
4. E F minus F G greater-than E G: Here, we need to subtract the length of FG from EF and compare it to EG. Using the same lengths as before, 5 - 3 is equal to 2, which is less than 7. Therefore, this statement is false.
5. E G + E F less-than F G: To check this statement, we need to compare the lengths of EG and EF combined with FG. Using the same lengths as before, 7 + 5 is equal to 12, which is greater than 3. Therefore, this statement is true.
Complete question :-
(8,5) and (x, -1); slope: -6
Answer:
9 = x; (9, -1)
Step-by-step explanation:
-y₁ + y₂\-x₁ + x₂ = m
-5 - 1\-8 + x
-8 + x = 1
+8 + 8
_________
x = 9
The denominator is set to equal one because the numerator already equals negative six, and all we have to do is divide it by a POSITIVE one to stay at negative six.
I am joyous to assist you anytime.
a bycicle tire completes 9/10 of a revolution every 1/3 of a second. how many revolutions will the tire complete every minute?
Answer:
162 RPM
Step-by-step explanation:
Start by multiplying 9⁄10 by the Multiplicative Inverse of ⅓, which is 3:
9⁄10 ÷ ⅓ → 9⁄10 × 3 = 2 7⁄10
After this, multiply the result by sixty seconds, since there are sixty seconds in one minute:
60 × 2 7⁄10 = 162
So, it will make 162 RPM.
I am joyous to assist you anytime.
How many centimeters are in 9.49
Answer:
949 centimeters
Step-by-step explanation:
100 centimeters = 1 meter
We have to multiply by 100 to find the values
9.49 meters = 9.49 * 100 = 949 m
Answer:
949 cm.
Step-by-step explanation:
1 m. = 100 cm.
100 × 9,49 = 949
⤻⤻
According to the Power of 10 rule, whenever you divide by 10 [⅒], you move the decimal mark to the left each time, and of course, whenever you multiply by 10, you move the decimal mark to the right each time. In this case, since you are multiplying by 100, you move the decimal mark twice to the right to get 949.
I am joyous to assist you anytime.
HELP!
Find negative square root of 36. (4 points)
A. 18
B. ±6
C. −6
D. 6
Answer:
c
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
Which of the following correctly names one of the vertices of the triangle
below?
ОА. 2
O B. LI
O c.
D. AZLM
Answer:
/\zlm is the correct answer for this kind of questions because the other answer over there aren't having any truth
the volume of a box is 400in3. if the height is 10in and the length is 8in, what is the width of the box (volume=l•w•h)
5in,
10in,
17in,
or 22in?
Final answer:
By rearranging the formula for the volume of a box to solve for width and substituting the given values, the width of the box is calculated to be 5 inches.
Explanation:
The student asks what the width of the box is, given that the volume of the box is 400 cubic inches (in³), the height is 10 inches (in), and the length is 8 inches (in). The formula to find the volume of a rectangular box is V = l × w × h, where V is the volume, l is the length, w is the width, and h is the height. Since we already have the volume, length, and height, we can rearrange the formula to solve for the width w as follows: w = V / (l × h). Substituting the given values, we get w = 400 in³ / (8 in × 10 in), which simplifies to w = 400 in³ / 80 in². After dividing 400 by 80, the result is w = 5 in. Therefore, the width of the box is 5 inches.
Use a distributive property to rewrite (4+5)6
Answer:
54
Step-by-step explanation:
First you would distribute 6 into 4 and 5. 6 times 5 is 30, and 4 times 6 is 24. the equation is now (24 + 30), which equals 54.
HELP PLEASE !
Consider the graph of the linear function hy
5. Which could you change to move the graph down 3 uns?
the value of b to-3
the value of m to -3
the value of b to 2
the value of m to 2
Answer:
b=2
Step-by-step explanation:
Changing the y-intercept would move the graph down or up.
So we have the equation [tex]y=\frac{-2}{3}x+5[/tex].
We want to move the graph down 3 units. We want the y-intercept to be 3 units lower than what is was. Since 5-3 is 2, then the new y-intercept is 2.
The equation would then be [tex]y=\frac{-2}{3}x+2[/tex].
So b=2.
What is the length of AB if A(-3,-4) B(-1,-6) C(-5,-8)
Answer:
AB = 2[tex]\sqrt{2}[/tex]
Step-by-step explanation:
Calculate the length using the distance formula
d = √ (x₂ - x₁ )² + (y₂ - y₁ )²
with (x₁, y₁ ) = A(- 3, - 4) and (x₂, y₂ ) = B(- 1, - 6)
AB = [tex]\sqrt{(-1+3)^2+(-6+4)^2}[/tex]
= [tex]\sqrt{2^2+(-2)^2}[/tex]
= [tex]\sqrt{4+4}[/tex]
= [tex]\sqrt{8}[/tex] = 2[tex]\sqrt{2}[/tex] ≈ 2.83 ( to 2 dec. places )
Answer:
Step-by-step explanation:
AB= √((-6+4)²+(-1+3)²)² = √(4+4)= √8 =2√2
find the solutions to the equation below x^2-25=0
Answer:
x = 5, -5
Step-by-step explanation:
Find the roots of [tex]x^{2} -25=0[/tex] by solving for x.
Add 25 to both sides
[tex]x^{2} =25[/tex]
Square root both sides
[tex]x = 5[/tex]
[tex]x=-5[/tex]
The solution to the quadratic equation x² - 25 = 0 is 5, -5 after using the identity a² - b² = (a + b)(a - b).
What is a quadratic equation?Any equation of the form [tex]\rm ax^2+bx+c=0[/tex] where x is variable and a, b, and c are any real numbers where a ≠ 0 is called a quadratic equation.
As we know, the formula for the roots of the quadratic equation is given by:
[tex]\rm x = \dfrac{-b \pm\sqrt{b^2-4ac}}{2a}[/tex]
It is given that:
The quadratic equation:
x² - 25 = 0
As we know,
a² - b² = (a + b)(a - b)
Using the above identity:
x² - 5² = 0
(x + 5)(x - 5) = 0
x + 5 = 0
x = -5
Or
x - 5 = 0
x = 5
We can also find the solution to the equation x² - 25 = 0 using the quadratic formula.
Thus, the solution to the quadratic equation x² - 25 = 0 is 5, -5 after using the identity a² - b² = (a + b)(a - b).
Learn more about quadratic equations here:
brainly.com/question/2263981
#SPJ2
Solve for x 10-4x=-9
Answer:
x = 4.75 or 19/4 or 4 and 3/4
Step-by-step explanation:
10 - 4x = -9
-10 -10
-4x = -19
---- -----
-4 -4
x = 4.75 or 19/4 or 4 and 3/4
Correct answer: x= - 3/2
Solve the equation for X x+3/6 = x - 6 /3
The equation x + 3/6 = x - 6/3 cannot be solved for x, as simplification leads to 1/2 = -2, which is not possible, indicating a mistake in the provided equation.
Explanation:To solve the equation x + 3/6 = x - 6/3 for x, let's first simplify each side of the equation by reducing the fractions. This gives us:
x + 1/2 = x - 2
At this point, we can see that the variable x appears on both sides of the equation. To solve for x, we would normally try to isolate x on one side. However, if we attempt to subtract x from both sides, we will get:
1/2 = -2
This statement is not true, indicating that the original equation was incorrect or improperly written. If the equation only involved x on one side, we could use algebraic techniques to solve for x, but as it stands with this impossible equality, we cannot find a value for x that satisfies the equation. Therefore, it seems there may be a mistake in the transcription of the original problem.
how to calculate ratio
Your Question: How to calculate ratio.
The Answer/Explanation: To find an equal ratio, you can either multiply or divide each term in the ratio by the same number (but not zero). For example, if we divide both terms in the ratio 3:6 by the number three, then we get the equal ratio, 1:2.
To calculate the ratio, the width will be divided by the GCD and the height will be divided by the GCD. A colon will be placed between those two numbers. The result is 4:3 -- the ratio for those screen dimensions.
Remember to check study guides, lessons and notes to rely on; working hard is the way to success. Good Luck!
To calculate a ratio, you compare two quantities and express their relationship as a fraction, a colon-separated pair, or a "to" statement. You usually divide the larger number by the smaller and simplify to whole numbers to find the smallest whole-number ratio.
To calculate a ratio, you compare two quantities to each other. Ratios can be represented in a few different ways, such as fractions, with a colon, or with the word "to". For example, a ratio might be 2/3, 2:3 or "2 to 3". If you're dealing with a scenario where you are given two different molar amounts, you would follow these steps:
Identify the molar amounts that you want to compare.Divide the larger molar amount by the smaller molar amount, which gives you a preliminary ratio. If the resulting numbers are not whole numbers, you can convert the numerator to an improper fraction if needed, and then simplify to get whole numbers.Verify your result, ensuring that the ratio is expressed as the smallest possible whole numbers that maintain the proportion between the two quantities.For example, if you're looking at a chemical equation and need to determine the mole ratio, divide all numbers by the smallest value presented. So, if the molar amounts are 5.5, 1, and 1.2, dividing each by the smallest amount (1 in this case) gives you the mole ratio of 5.5:1:1.2. Simplified, it would become 55:10:12 as a ratio of whole numbers.
I need this done tonight. please help
Check the picture below.
notice, the car starts at 0 miles and 0 minutes, since it was at rest, wasn't moving, and off it went and in 10 minutes it has covered 55 miles.
jamie buys 5 books for $7 each draw an array and write a multiplication equation to find the total cost of the book
Answer:
The total cost of book using array multiplication is 35$
Solution:
Jamie buys 5 books for 7$. So draw array multiplication table using 5 rows and 7 columns (see the figure attached below)
By counting the number of rows and number of objects in each row from the figure attached below, we get the total cost of the book.
Total cost = number of rows [tex]\times[/tex] total number of objects in each row
Total cost = 5 [tex]\times[/tex] 7 = 35
Prove that the quadrilateral with vertices (2,5) (4,8) (7,6) and (5,3) is a rectangel
Answer: Line slopes:
m1= 3/2 defined by points (5,3) and (7,6)
m2= -2/3 defined by points (7,6) and (4,8)
m3 = 3/2 defined by points (4,8) and (2,5)
m4 = -2/3 defined by points (2,5) and (5,3)
All comply the orthogonal slopes rule (90º)
Step-by-step explanation:
As those 4 point define a polygon, to check is that polygon is a rectangle, you need to compare the slopes of the lines defined by the 4 points and check that accomplish the following rule:
m1 = -(1/m2). this shows that the slopes are intersected in 90º angle.
Final answer:
By calculating the dot products of the direction vectors for adjacent sides, all of which are zero, and checking the distances of opposite sides, which are equal, we prove that the given quadrilateral is a rectangle.
Explanation:
To prove that a quadrilateral with given vertices is a rectangle, we must show that the quadrilateral has four right angles and opposite sides are equal. A right angle exists between two sides if the dot product of their direction vectors is zero, as this indicates perpendicularity. Equal length of opposite sides can be shown by the distance formula. We are given the vertices of the quadrilateral: (2,5), (4,8), (7,6), and (5,3).
Calculate the direction vectors of adjacent sides:
AB: (4-2, 8-5) = (2,3)
BC: (7-4, 6-8) = (3,-2)
CD: (7-5, 6-3) = (2,3)
DA: (2-5, 5-3) = (-3,2)
Check the dot products of the direction vectors of adjacent sides to confirm right angles:
AB · BC = (2)(3) + (3)(-2) = 6 - 6 = 0
BC · CD = (3)(2) + (-2)(3) = 6 - 6 = 0
CD · DA = (2)(-3) + (3)(2) = -6 + 6 = 0
DA · AB = (-3)(2) + (2)(3) = -6 + 6 = 0
Use the distance formula to confirm equal lengths of opposite sides:
AB = √((4-2)² + (8-5)²) = √(13)
CD = √((7-5)² + (6-3)²) = √(13)
BC = √((7-4)² + (6-8)²) = √(13)
DA = √((2-5)² + (5-3)²) = √(13)
Since all adjacent sides are perpendicular and opposite sides are of equal length, the quadrilateral is a rectangle.
A faucet is leaking at a rate of 4.2 milliliter per minute. How many gallons of water does the faucet leak per day? Use 1 L = 0.26 gal. Explain how you solved this problem
To find out the volume of water leaked per day by a leaking faucet, we convert the given rate from milliliters per minute to gallons per day. The faucet leaks at a rate of 4.2 milliliters per minute. By multiplying this rate by the number of minutes in a day, we find that it leaks 6048 milliliters per day. After converting milliliters to liters and liters to gallons using conversion factors, we determine that the faucet leaks 1.57328 gallons of water per day.
Explanation:To find out how many gallons of water the faucet leaks per day, we need to determine the volume in milliliters and convert it to gallons. The given rate is 4.2 milliliters per minute, so we need to find the number of minutes in a day. There are 60 minutes in an hour and 24 hours in a day, so there are 60 x 24 = 1440 minutes in a day.
Multiplying the rate by the number of minutes in a day, we get 4.2 x 1440 = 6048 milliliters per day. To convert milliliters to liters, we divide by 1000, so 6048 / 1000 = 6.048 liters per day. Finally, to convert liters to gallons, we multiply by the conversion factor 0.26, resulting in 6.048 x 0.26 = 1.57328 gallons per day.
Learn more about Converting units of volume here:https://brainly.com/question/31428833
#SPJ2
The following pairs of equations are equivalent. Describe the operation that occurred in the second equation. 3+9=12 and 3+9-5=12-5
Answer:
See explanation
Step-by-step explanation:
A. Given the equation
[tex]3+9=12[/tex]
Using the subtraction property of equality (subtracting 5 from both sides of equation), we'll get an equivalent equation
[tex]3+9-5=12-5[/tex]
B. Given the equation
[tex]x-4=7[/tex]
Using the addtion property of equality (adding 4 to both sides of equation), we'll get an equivalent equation
[tex]x-4+4=7+4[/tex]
C. Given the equation
[tex]2(6)=12[/tex]
Using the division property of equality (dividing both sides of equation by 2), we'll get an equivalent equation
[tex]\dfrac{2(6)}{2}=\dfrac{12}{2}[/tex]
D. Given the equation
[tex]\dfrac{x}{2}=5[/tex]
Using the multiplication property of equality (multiplying both sides of equation by 2), we'll get an equivalent equation
[tex]2\cdot \dfrac{x}{2}=2\cdot 5[/tex]
The operation displayed in the equation change from '3 + 9 = 12' to '3 + 9 - 5 = 12 - 5' is subtraction. The number 5 is subtracted from both sides of the original equation, altering the values while keeping the equation fundamentally equivalent and balanced.
Explanation:The operation that occurred between the two equations, 3 + 9 = 12 and 3 + 9 - 5 = 12 - 5, is called subtraction. This operation is depicted by the inclusion of the -5 in both sides of the second equation. Essentially, the number 5 is being subtracted from the results of the first equation, resulting in an altered but comparable equation.
Think of it as taking the entire set of operations in the first equation, and applying an additional step to it - the step of subtracting 5, denoted in the equation as '- 5'. This step is applied to both sides of the equation to maintain its balance, keeping it equivalent to the initial equation, albeit with different values.
Continuing from our first equation, the left-hand side which was '3 + 9' (equals to 12) would become '3 + 9 - 5' (equals to 7), and the right-hand side which was '12', becomes '12 - 5' (also equals to 7). The fundamental rule being employed here is that the same operation should be performed on both sides of an equation to keep it balanced. Adjusting only one side would result in a different, non-equivalent equation.
Learn more about Subtraction in Equations here:https://brainly.com/question/28832353
#SPJ3
what is the answer to -2 (6n-5) = 26? PLEASE ANSWER CORRECTLY
Answer:
n = 1.33 repeating
Step-by-step explanation:
first you distribute the -2 by everything in the parenthesis so then you get -12 + 1- = 26 the you subtract 10 from each side which leaves you with -12 = 16 then you devide -12 by both sides and you get the decimal 1.33 repeating.
Factor the polynominal. t^2+8t
Answer:
t = 8 t = 0
Step-by-step explanation:
The factored form is t(t + 8).
Certainly! Let's factor the given polynomial t^2 + 8t step by step.
Identify Common Factors: Factor out the common factor, which is t in this case.So, the factored form of t^2 + 8t is t(t + 8).